A Leaderless Hierarchical Atomic Broadcast Algorithm - Ruchel, Lucas V.; Rodrigues, Luiz Antonio; Turchetti, Rogério C.; Arantes, Luciana; Duarte Jr., Elias P.; Camargo, Edson (Anais do Latin-American Symposium on Dependable Computing (LADC), 2022)
This work presents LHABcast, a Leaderless Hierarchical Atomic Broadcast algorithm that is fully decentralized and allows all processes to send messages simultaneously. Processes use autonomic spanning trees built on top of the VCube overlay network to propagate message timestamps, i.e., local sequence numbers. Processes can fail by crashing. After each process receives the timestamps, it can make a decision about the message delivery sequence. The algorithm is shown to be correct.